脑啡肽酶和脑啡肽酶抑制剂对葡萄糖稳态的影响:一个有争议的观点和有前景的领域 - Faisal Holil AlAnazi; Hayder M. Al‐kuraishy; Ali I. Al‐Gareeb; Athanasios Alexiou; Marios Papadakis; Hanan A. Ogaly; Yousef Abud Alanazi; Hebatallah M. Saad; Gaber El‐Saber Batiha (Journal of Diabetes, 2023)
Abstract Neprilysin (NEP) is a transmembrane zinc‐dependent metalloproteinase that inactivates various peptide hormones including glucagon‐like peptide 1 (GLP‐1). NEP inhibitors may be effective in the management of type 2 diabetes mellitus (T2DM) by increasing the circulating level of GLP‐1. However, acute‐effect NEP inhibitors may lead to detrimental effects by increasing blood glucose independent of GLP‐1. These findings suggest a controversial point regarding the potential role of NEP inhibitors on glucose homeostasis in T2DM patients. Therefore, this perspective aimed to clarify the controversial points concerning the role of NEP inhibitors on glucose homeostasis in T2DM. NEP inhibitors may lead to beneficial effects by inhibition of NEP, which is involved in the impairment of glucose homeostasis through modulation of insulin resistance. NEP increases dipeptidyl peptidase‐4 (DPP4) activity and contributes to increasing active GLP‐1 proteolysis so NEP inhibitors may improve glycemic control through increasing endogenous GLP‐1 activity and reduction of DPP4 activity. Thus, NEP inhibitors could be effective alone or in combination with antidiabetic agents in treating T2DM patients. However, long‐term and short‐term effects of NEP inhibitors may lead to a detrimental effect on insulin sensitivity and glucose homeostasis through different mechanisms including augmentation of substrates and pancreatic amyloid deposition. These findings are confirmed in animal but not in humans. In conclusion, NEP inhibitors produce beneficial rather than detrimental effects on glucose homeostasis and insulin sensitivity in humans though most of the detrimental effects of NEP inhibitors are confirmed in animal studies.